Computational mathematics applied to astrophysics: Three cases of study. (September 2019) - Arceo Díaz, S; Bricio Barrios, E E; Schröder, K P; Zuber, K; Jack, D; Verduzco Ramírez, J A
Abstract: The role of computational mathematics on the study of the fundamental properties of neutrinos and axions and their impact on the energy loss within stellar structure is illustrated in this work. The theoretical predictions, done with the aid of a numerical code for simulating stellar evolution, are used in three cases of interest: the number of neutrinos reaching our planet from the closest stellar system, calculated by modelling its two main stars and their corresponding neutrino spectrum; the magnitude of the neutrino magnetic dipole moment and the axion-electron coupling constant is estimated by comparing stellar models to the tip-RGB of fifty globular clusters; and, finally, the survival of the Earth, after the Sun becomes a red giant is tested for an scenario in which axions and neutrinos are being simultaneously produced within the solar core.